2015
DOI: 10.1021/acssuschemeng.5b00646
|View full text |Cite
|
Sign up to set email alerts
|

Injection Molded Sustainable Biocomposites From Poly(butylene succinate) Bioplastic and Perennial Grass

Abstract: Biocomposites from poly(butylene succinate) (PBS) and perennial grass (miscanthus fibers) were successfully prepared by extrusion and injection molding methods with different fiber loadings. The tensile strength of uncompatibilized PBS/miscanthus composites was much lower compared to that of neat PBS. Unlike tensile strength, the flexural and impact strengths were significantly enhanced after incorporation of miscanthus fibers into the PBS matrix. The enhanced flexural strength was attributed to the reinforcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
89
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 56 publications
16
89
0
Order By: Relevance
“…These properties are comparable with other agro fibers such as hemp and sisal . However, only few researchers have been investigated the performance of miscanthus fiber reinforced composites with biodegradable polymers . Johnson et al .…”
Section: Introductionmentioning
confidence: 85%
“…These properties are comparable with other agro fibers such as hemp and sisal . However, only few researchers have been investigated the performance of miscanthus fiber reinforced composites with biodegradable polymers . Johnson et al .…”
Section: Introductionmentioning
confidence: 85%
“…PBS has mechanical properties comparable to polyolefins like PE and PP . PBS has relatively good processability and can be processed via a broad range of conventional techniques (i.e., sheet extrusion, injection molding, thermoforming, blow molding, foaming, fiber spinning, and filament) for food packaging and dinnerware applications . PBSA is produced from succinic acid, 1,4‐butanediol, and adipic acid monomers by copolymerization.…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…This reduction is commonly observed for most of the ber reinforced composites. 11,18 However, all the compatibilized composites exhibited slightly higher elongation at break compared to their corresponding uncompatibilized composites. This implies that the interfacial adhesion was improved between the phases.…”
mentioning
confidence: 95%
“…Although, only a few studies have investigated the miscanthus ber reinforced biodegradable polymer composites. 4,8,9,17,18 In our previous study 18 we have used MAH graed PBS compatibilizer to improve the compatibility between PBS matrix and miscanthus ber. Due to the increased compatibility between the matrix and ber, it was found that the mechanical performances of the resulting composites were superior compared to the uncompatibilized counterparts.…”
mentioning
confidence: 99%